Race in France : interdisciplinary perspectives on the politics of difference - Chapman, Herrick; Frader, Laura Levine, 1945- (Berghahn Books, 2004)
"Scholars across disciplines on both sides of the Atlantic have recently begun to open up, as never before, the scholarly study of race and racism in France. These original essays bring together in one volume new work in history, sociology, anthropology, political science, and legal studies. Each of the eleven articles presents fresh research on the tension between a republican tradition in France that has long denied the legitimacy of acknowledging racial difference and a lived reality in which racial prejudice shaped popular views about foreigners, Jews, immigrants, and colonial people. Several authors also examine efforts to combat racism since the 1970s."--